Islamic banking-growth nexus: evidence from Toda-Yamamoto and bootstrap granger causality test - Abdul Manap, Turkhan Ali; Abduh, Muhamad; Omar, Mohd. Azmi (IIUM Institute of Islamic Banking and Finance, 2012)
This paper examines the causal relationship between Islamic banking development and economic growth and between Islamic banking development and capital formation in the case of Malaysia. Different with other studies, this paper uses Toda-Yamamoto and bootstrap granger non-causality test to reduce the size distortion in the data and provide more precise test inference than the commonly used asymptotic method especially in the case of small sample size. The results demonstrate a significant Granger causality from Islamic financial development to economic growth but the converse is not true, which supports the Schumpeter’s supply-leading view. The empirical evidence indicates further development of Islamic finance will contribute to the economic growth in the case of Malaysia.